2013
DOI: 10.1186/1476-511x-12-151
|View full text |Cite
|
Sign up to set email alerts
|

The role of 14,15-dihydroxyeicosatrienoic acid levels in inflammation and its relationship to lipoproteins

Abstract: Background14,15-Epoxyeicosatrienoic acids (14,15-EETs) generated from arachidonic acid by cytochrome P450 epoxygenases have beneficial effects in certain cardiovascular diseases, and increased 14,15-EET levels protect the cardiovascular system. 14,15-EETs are rapidly hydrolyzed by soluble epoxide hydrolase (sEH) to the corresponding 14,15-dihydroxyeicosatrienoic acids (14,15-DHETs), which are generally less biologically active but more stable metabolite. A functionally relevant polymorphism of the CYP2J2 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…In arachidonate cascade, the P450 epoxygenase is unique in regio- and stereochemical selectivity to biosynthesize EET mediators. EETs are known to reduce infarct size, preserve LV function and limit cardiac hypertrophy [35, 36]. CYP2J subfamilies of CYP are abundantly expressed in the cardiovascular system and metabolize AA to produce four biologically active EETs: 5,6 (cypoxins; CExn1)-, 8,9 (CExn2)-, 11,12 (CExn3)-, and 14,15 (CExn4)-EETs [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In arachidonate cascade, the P450 epoxygenase is unique in regio- and stereochemical selectivity to biosynthesize EET mediators. EETs are known to reduce infarct size, preserve LV function and limit cardiac hypertrophy [35, 36]. CYP2J subfamilies of CYP are abundantly expressed in the cardiovascular system and metabolize AA to produce four biologically active EETs: 5,6 (cypoxins; CExn1)-, 8,9 (CExn2)-, 11,12 (CExn3)-, and 14,15 (CExn4)-EETs [37].…”
Section: Discussionmentioning
confidence: 99%
“…These results the align with the results from Yang et al . [35] where a decrease in EETs generated an inflammatory response in coronary heart disease (CHD) patients. Other clinical studies have also shown obstructive coronary artery disease (CAD) is associated with lower EET metabolite levels [38].…”
Section: Discussionmentioning
confidence: 99%
“…AA oxygenation by cytochrome P450 forms epoxyeicosatrienoic acids, and epoxide hydrolase subsequently results in formation of the more stable 14,15-DHETs (Figure 1). These compounds have been associated with pro-inflammatory processes [36, 37]. Neither 14,15-S and 14,15-R DHET were significantly altered by diet in normal tissues, but both products were reduced in colon tumors of fish oil-fed animals versus that of Western fat-fed animals (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay (ELISA) was used to measure the plasma 14, 15-DHET (14, 15-DHET ELISA kit; Detroit R&D Inc., Detroit, MI, USA) according to the manual. 26…”
Section: 15-dhet Measurementsmentioning
confidence: 99%